Psychology research in women`s soccer: a scoping review - Gredin, N. V.; Kryger, K. O.; McCall, A.; Solstad, B. E.; Torstveit, M. K.; Massey, A.; Ivarsson, A. (Science and Medicine in Football, 2025)
Previous research suggests that psychological factors play an important role in trying to explain and predict the participation, performance, and health of player and practitioners in soccer. However, most previous works have focused on specific research questions and included samples from male populations. As part of a larger Fédération Internationale de Football Association (FIFA) project aiming to steer women`s soccer research, our purpose with this scoping review was to give an overview of the current state of psychology-related research within women`s soccer. We searched five electronic databases up to April 2023, from which 280 original peer-reviewed articles met the inclusion criteria. Included records were inductively coded into 75 specific research topics and nine broader research categories. Population characteristics within each topic and category, and overall publication trends, were identified. The results revealed a growth in research attention, with notable increases in publication rates around the international competitions years, over the last two decades. While a notable number of abstracts did not report sufficient details about population age and/or playing levels, senior elite players were identified as the most common population studied. Most studies examined several topics from different research categories, with research focusing on emotions, moods and/or environmental factors, and the specific the topics of anxiety, stress, and coach behavior, receiving most research attention. Our study provides an informative mapping of all psychology-related research activity within women`s soccer, which will enhance researchers` understanding of the current quantity of literature within this complex, heterogeneous, and growing area of research.